Evaluation of osteoblast viability, alkaline phosphatase production and collagen secretion in the presence of hydroxyapatite reinforced with oxide glasses - (:unkn) unknown (Trans Tech Publications Ltd, 2005)
Two (45.5 wt % P2O5, 54.5 wt% CaO) and three (45 wt % P2O5, 28 wt% CaO, 27wt% Na2O) oxide glasses, sinterizing at 1200 and 1300°C[2] showed an increase on cell viability and proliferation.
Keywords: Alkaline phosphatase; Collagen; Hydroxyapatite; Osteoblasts; Three oxides; Two oxides